A Systematic Literature Review of Models, Technologies, and Global Impacts in Inclusive Education in the Digital Age - Said, Hasmira; Ampa, Andi Tenri; Aziz, Fatimah; Nongko, Pahenra A (PPSDP International Journal of Education, 2025)
Inclusive education faces persistent challenges related to resource gaps and social isolation. The post-pandemic convergence with digital technologies and the need for novel collaborative models present a transformative opportunity, yet no systematic review has holistically integrated these three core elements. This Systematic Literature Review (SLR) aims to map the collaborative models, technological roles, and critical success factors for implementing technology-mediated collaborative inclusive education. Following the PRISMA protocol, searches were conducted in Scopus, Web of Science, and ERIC databases (2019-2024). From an initial pool of 2,348 articles, 48 met the inclusion criteria for thematic analysis. The review identified three innovative models: (1) Global Collaboration Networks connecting students across geographical boundaries; (2) AI-Powered Personalization & Peer Matching for optimal learning group formation; and (3) Digital Community-Engaged Projects. Technologies such as AI and Extended Reality (XR) acted as catalysts for personalization and empathy simulation. Key enabling factors were visionary leadership and teacher training, while primary challenges included the digital divide and algorithmic bias.  The findings signify a paradigm shift towards “Inclusion through Distributed Digital Collaboration.” This integration has a high impact on democratizing access and creating authentic, inclusive learning experiences. Future research should focus on AI ethics, implementation in low-resource settings, and exploring immersive technologies like the Metaverse.